A Case Report: Management Obstetric Ureterocervicovaginal Fistula with Psoas Hitch Technique - Rizqi Rachman, Ary; Irianta, Trika; Utama Pelupessy, Nugraha (International Journal of Psychosocial Rehabilitation, 2020)
Urogenital fistula is one of the causes of women’s decreasing quality of life. The woman’s inability to urinate normally will greatly disrupt the life of the woman herself throughout her life if it does not receive serious attention. The prevalence of fistulas is 1 in 1000 women and the largest in developing countries. It is associated with labor, pelvic organ malignancies, radiation, and complications of operation. Mrs. M, 32 years old, Parity 2 Abortus 1, came with the chief complaint of urinary seeping from the genitals for three months. She had a history of cesarean section surgery 3 months ago. The results of the methylene blue test were negative. Abdominal CT scans with contrast were performed, and left urethra with urethritis were found. We diagnosed ureterocervicovaginal fistula. During surgery, a ureterocervicovaginal fistula was found on the left, and an abdominal ureteroneocystotomy was performed with the Psoas Hitch technique and the Lich Gregoir technique. There were no postoperative complications and recurring complaints related to urinary incontinence, and the result of the abdominal CT scan with contrast after 2 months did not show contrast extravasation of the left ureter. Psoas Hitch Technique is one of the managements in cases of ureterocervicovaginal fistula.